Untying the Mediterranean Gordian Knot: A Twenty First Century Challenge for Fisheries Management - Vielmini, Ilaria; Perry, Allison L.; Cornax, María José (Frontiers in Marine Science, 2017)
Management of fisheries in the Mediterranean basin has often been described as a unique and complex challenge, due to their multi-specificity, the diversity of gear-types, and the number of nations involved. This perspective has gone hand-in-hand for decades with a lack of strong political will from decision-makers, who have been unwilling to put Mediterranean fisheries management high on their agendas. Over time, exploitation rates of demersal stocks have increased and in 2016, 97% of shared stocks assessed in the Mediterranean were reported to be overfished. An alarm bell about the chronic overfishing of Mediterranean fish stocks was rung by European policy makers in 2015, exactly 20 years after the Code of Conduct for Responsible Fisheries adopted by the Food and Agriculture Organization mandated that states should ensure the sustainable use of fishery resources. In this perspective, we: (i) review the context of fisheries management in the Mediterranean; (ii) identify the potential factors that may have hindered management and; (iii) discuss how the reformed European Union Common Fisheries Policy and the binding commitments laid down in its text may lead to knock-on effects for fisheries management in the international Mediterranean context, if properly implemented. In this line, we also present the example of demersal fisheries management in the Strait of Sicily, which may represent a starting point for science-based management in the Mediterranean.